Gene targeting in polymerase theta‐deficient Arabidopsis thaliana. (18th November 2021) - van Tol, Niels; van Schendel, Robin; Bos, Alex; van Kregten, Maartje; de Pater, Sylvia; Hooykaas, Paul J.J.; Tijsterman, Marcel
SUMMARY: Agrobacterium tumefaciens ‐mediated transformation has been for decades the preferred tool to generate transgenic plants. During this process, a T‐DNA carrying transgenes is transferred from the bacterium to plant cells, where it randomly integrates into the genome via polymerase theta (Polθ)‐mediated end joining (TMEJ). Targeting of the T‐DNA to a specific genomic locus via homologous recombination (HR) is also possible, but such gene targeting (GT) events occur at low frequency and are almost invariably accompanied by random integration events. An additional complexity is that the product of recombination between T‐DNA and target locus may not only map to the target locus (true GT), but also to random positions in the genome (ectopic GT). In this study, we have investigated how TMEJ functionality affects the biology of GT in plants, by using Arabidopsis thaliana mutated for the TEBICHI gene, which encodes for Polθ. Whereas in TMEJ‐proficient plants we predominantly found GT events accompanied by random T‐DNA integrations, GT events obtained in the teb mutant background lacked additional T‐DNA copies, corroborating the essential role of Polθ in T‐DNA integration. Polθ deficiency also prevented ectopic GT events, suggesting that the sequence of events leading up to this outcome requires TMEJ. Our findings provide insights that can be used for the development of strategies to obtain high‐quality GT events in crop plants. Significance Statement: We find that homologous recombination‐mediated gene targeting (GT) in polymerase theta (Polθ)‐deficient Arabidopsis exclusively produces plants that contain true GT events and are devoid of random T‐DNA integration. These observations corroborate the crucial role for Polθ in T‐DNA integration, and reveal that Polθ‐mediated end joining is essential for ectopic GT, which is a prominent outcome in Polθ‐proficient plants.